Efficient enzymatic degradation of poly (ɛ-caprolactone) by an engineered bifunctional lipase-cutinase. (February 2019) - Liu, Min; Zhang, Tianrui; Long, Liangkun; Zhang, Rui; Ding, Shaojun
Abstract: Lipases and cutinases belong to esterase family and can be used as biocatalysts for poly (ɛ-caprolactone) (PCL) degradation and recycling. A number of synthetic fusion enzymes with two or more catalytic domains were reported to be superior to the parental enzymes or their mixture for many biotechnological applications but rarely for the polyester biodegradation. To develop a more efficient biocatalyst for poly (ɛ-caprolactone) (PCL) degradation and recycling, a bifunctional lipase-cutinase (Lip-Cut) constructed by end-to-end fusion was successfully overexpressed in Pichia pastoris with 0.9% of methanol induction at pH 6.0 and temperature 27 °C. Lip-Cut displayed more efficient poly (ɛ-caprolactone) degradation capability, and the weight loss of PCL film by Lip-Cut at 6 h was 13.3, 11.8 and 5.7 times higher than that by Lip, Cut and Lip/Cut mixture, respectively. GC-MS analysis of the degraded products of PCL revealed that the mainly degraded product was 6-hydroxyhexanoic acid and small ratio of ɛ-caprolactone. Our results demonstrated that the proper construction of bifunctional lipase-cutinase could enhance the synergistic action of two moieties due to the complementary properties of both enzymes in substrate specificity and hydrolysis pattern. The method provided an effective approach to engineer more efficient biocatalyst for bio-application in degradation and recycling of PCL. Highlights: A bifunctional Lip-Cut was successfully overexpressed in Pichia pastoris . Lip-Cut exhibited 13.3, 11.8 and 5.7 times higher PCL degradation capacity than Lip, Cut and mixture at 6 h. The mainly degraded product was ɛ-hydroxyhexanoic acid and small ratio of ɛ-caprolactone. Lip-Cut could be an efficient biocatalyst for bio-application in degradation and recycling of PCL.